INTEGRASI DIALOG SOCRATIC DAN DEEP LEARNING DALAM PEMBELAJARAN BERBASIS ISU LINGKUNGAN: PENGUATAN KOMPETENSI KEWARGANEGARAAN SISWA SEKOLAH DASAR - Chesqi Arnetta Fadhilla P.S; Raden Roro Setyowati; Putri Rachmadyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of Socratic dialogue and the deep learning approach in environmental issue-based learning as an effort to strengthen elementary school students’ citizenship competencies. The study is grounded in the need to develop citizenship learning that not only emphasizes conceptual understanding but also fosters critical thinking, social responsibility, active participation, and students’ ecological citizenship awareness. This research employed a descriptive qualitative approach with a field study design involving fourth-grade students at SDI A-Education. The data sources consisted of primary data obtained from teachers and fourth-grade students, as well as secondary data derived from learning documents and supporting literature. Data were collected through observation, interviews, and documentation, while data analysis employed an interactive model involving data reduction, data display, and conclusion drawing to obtain an in-depth understanding of the implementation of the learning process. The findings reveal that the integration of Socratic dialogue and deep learning based on environmental issues enhances student engagement through reflective activities, collaborative discussions, and problem-solving practices related to real environmental issues within the school context. Furthermore, the learning approach contributes significantly to strengthening students’ citizenship competencies, particularly in critical thinking, social responsibility, cooperation, collaborative skills, active participation, and environmental awareness as a form of civic practice. Although challenges were identified, including students’ limited abstract reasoning abilities and teachers’ readiness to facilitate dialogical learning, contextual strategies and scaffolded reflective questioning proved effective in optimizing the learning process. This study concludes that the integration of Socratic dialogue and deep learning through environmental issue-based learning represents an effective pedagogical approach to strengthening elementary school students’ citizenship competencies in a reflective, participatory, and contextual manner.